Correlation between Farmers' Activeness in Farmer Groups with Productivity and Income of Cocoa Farming in Trenggalek Regency - Hariyati, Yuli; Ria, Vina Yunita; Rahman, Rena Yunita; Ibanah, Indah; Rosyady, Muhammad Ghufron (International Journal on Food, Agriculture and Natural Resources, 2024)
The cocoa plantation in Suruh Village, Trenggalek Regency is the main supplier of cocoa beans to UPH Rumah Coklat owned by the Department of Agriculture and Food of Trenggalek Regency. For example, in cocoa farmers' participation in the "Tunggal Jaya" Farmers Group, farmers are taught to make rorak and worm palaces to deal with climate change which helps maintain soil moisture and increase fertility. The objectives of this study are to determine 1) the level of farmer activeness, 2) the level of productivity, 3) the level of income, and 4) the correlation between farmer activeness in farmer groups with productivity and income of cocoa farming in Suruh Village, Trenggalek Regency. The number of samples used was 111 respondents. Data analysis used the Likert scale, productivity analysis, income analysis, and Pearson correlation. The results of the study showed: 1) cocoa farmer activeness in farmer groups in Suruh Village, Trenggalek Regency is in the active category with an overall average score of 3.56; 2) the average productivity of cocoa farming is in the medium category at 0.54 tons/ha/year; 3) the average income of cocoa farming is Rp6,016,562/year; 4) the correlation between farmer activeness with productivity is 0.865, farmer activeness with income is 0.760, and productivity with income is 0.868. The direction of the three correlations is positive and significant.